Analysis and development of effective distance learning practices - Almazova, Irina G. (2021)
Distance education at the present stage of development of the world educational practice has acquired a global character. The range of educational services has significantly expanded; the number of educational organizations and institutions involved in this form of education has increased; a huge number of students use the Internet, gadgets and high-tech services. It has influenced the development of the educational environment around the world. Effective distance education practices are those forms of distance learning that allow students and other students to receive “remote” education via the Internet, if necessary. Such a necessity today has become the epidemiological situation in the world with the spread of infection caused by the coronavirus SARS-CoV-2 (2019-nCoV). The publication describes those practices that have proven to be effective. Their advantages and disadvantages are analyzed. The ways of developing such practices are determined taking into account a number of characteristic features of distance education: flexibility, modularity, innovative quality control of education, role repertoire of the teacher, economic benefits, etc. Describes specific principles of distance education, allocated based on the study of domestic and foreign authors, content updated by the authors: the principle of free access; the principle of remoteness; the principle of interactivity, the principle of identification; the principle of adequacy and expediency of using digital technologies in distance education. Methodological recommendations for teachers are given. The purpose of our research is to analyze how effective distance education and its forms are for students and primary school teachers who master additional professional training programs. Examples of questionnaires and survey data on the subject under study are given.